The Role of the Animal Characters in the Artistic World’s Creation in Beatrix Potter’s - Wdowińska, Monika (The Motifs of Fauna and Flora in Literature and Culture, 2018)
The aim of the article is an attempt to report the behaviour of the animal character and the variety of fauna which is a background of events in Potter’s Tales. The attention will be drawn on unusual animal characters embodying particular behaviour and manners of, most frequently, absurd and shallow people. The issue of real places — captured on original illustrations — which inspired the process of creating a fictional world will be traced. In the following part of the lecture the formation process of the character will be traced. Beatrix Potter was an excellent writer — strayed from fairy tale’s canon and common stereotype, in which given animal represents a certain feature, either positive or negative. Individual stories of Peter Rabbit, his cousin Benjamin Bunny, Squirrel Nutkin, Mittens and Mr. Jeremy Fisher will be finally tracked and proved. In the contemporary world it is worth doing some reflection on the humanity nature and on the role of values in the life of homo sapiens representative. The 21 st century, which is marked by superficiality, mental, but unreal process of aging, incapacity of creating, but first of all, caring about interpersonal relationships, encourages us to think about the “quality” of everyone’s existence.